Enhancing student career readiness: a two-decade systematic literature review - Dian Rachmawati; Sheerad Sahid; Mohd Izwan Mahmud; Nor Aishah Buang (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study intends to discover the elements that impact student career readiness growth, analyze the components that dominate that growth, and identify the factors that dominate student career readiness. The methods used to review selected articles are discussed including publication standards, databases, eligibility and exclusion criteria, stages of the review process (identification, screening, feasibility) as well as abstraction and analysis of data. By following the guidelines of item preferred reporting items for systematic reviews and meta-analyses (PRISMA) to produce this review. Based on the commonalities and traits of the first identified components, these factors have been separated into two categories, internal and external. Self-efficacy factors for internal factors and job training factors for external factors are the two factors with the maximum frequency and dominance over the others. Pursuing formal and non-formal education relevant to the chosen career field, making short-term and long-term career plans, establishing a strong professional network, and seeking relevant work experience through internships, part-time jobs, or volunteer work are all components of a career readiness strategy. Develop the necessary skills for an industry or career field, improve your communication skills, think positively, and be willing to confront career challenges. Maintain a balance between personal and professional life.